دراسة تأثيرمثبط النمو سيكوسيل (Chloro chline chloride ccc) في نموشتول البندورة تحت ظروف الزراعة المحمية - زيدان رياض (Latakia University Journal -Biological Sciences Series, 2019)
درس تأثير مثبط النمو سيكوسيل في نمو شتول البندورة (الهجين أمل ). من اجل ذلك جرى رش شتول البندورة في مرحلة الورقة الحقيقية الثالثة بمركب c c c بتركيز 750 و1000مغ/ ليتر لمرة واحدة، وبتركيز 250 ، 500 ,750 ، 1000مغ /ليتر لمرتين بفاصل 10 أيام بين الرشة والأخرى ،وذلك بهدف الحد من النمو الخضري لزيادة قدرة الشتول على تحمل الإجهاد الحراري الذي تتعرض له خلال فترة إعدادها في العروة الصيفية – الخريفية. جرى إعداد الشتول في أصص بلاستيكية قطرها 10سم بعد ملئها بالتورب ضمن بيت بلاستيكي وصممت التجربة وفق القطاعات العشوائية الكاملة بأربعة مكرارت للمعاملة الواحدة وبمعدل 10 نباتات في المكرر الواحد . نفذ البحث في منطقة بانياس ، محافظة طرطوس خلال الفترة الواقعة بين 1/6/2001 ولغاية 12/7/2001 (موعد التشتيل) . أظهرت النتائج أن الرش بمركب السيكوسيل لمرتين يعمل على الحد من استطالة الشتول، إذ انخفض طول الساق بنسبة تراوحت بين 65.75% عند رش النباتات بتركيز250مغ/ليترحتى048.3 % عند الرش بتركيز 1000مغ/ليتر،وذلك مقارنة مع الشاهد . كما أظهرت النتائج أيضا أن المعاملة بالمركب تسهم في زيادة قطرالساق والوزن الطازج والجاف للمجموع الخضري ،دون أن يكون لها تأثير في عدد الأوراق المتشكلة على النباتات مقارنة مع الشاهد. The effect of growth inhibitor "Cycocel" on tomato seedlings (Hybrid, Amal) was studied. The tomato seedlings were sprayed in third true leaf stage by CCC compound, in two concentrations (750 and 1000 mg /L) one time, and in four concentrations (250,500,750 and 1000 mg/L) twice with 10 days interval. The aim of these treatments was to decrease seedlings vegetative growth, in order to increase seedlings ability to support thermic stress during their development in summer-autumn period. The seedlings were grown in 10 cm diameter plastic pots, which contain peat moss. The pots were put in plastic green house. The trial was performed according to the Complete Randomized Block Design (10 seedlings/treatment and 4 replicates).The trials were effectuated in Baniass region (Tarots Department) during the period between 1st Jun and 12th July 2001 (plantation date). The results showed that, spraying the tomato seedlings with 250 mg / L. CCC solution decreased the stem length by 65,75% and 48,30% by spraying with concentration of 1000 mg / L., with remarkable increase of stem diameter, fresh and dry vegetation weight, without any effect on the number of seedlings leaves in comparison with the control plants.